Efficacy and safety of nabiximols cannabinoid medicine for paediatric spasticity in cerebral palsy or traumatic brain injury: a randomized controlled trial. (27th April 2020) - Fairhurst, Charlie; Kumar, Ram; Checketts, Daniel; Tayo, Bola; Turner, Susie
Abstract : Aim: To assess the efficacy, safety, and tolerability of oromucosal nabiximols cannabinoid medicine as adjunct therapy for children with spasticity due to cerebral palsy/traumatic central nervous system injury with inadequate response to existing treatment. Method: Overall, 72 patients (mean [SD] age 12y 4mo [3y 1mo], range 8‒18y) were randomized at a ratio of 2:1 to receive nabiximols ( n =47; 29 males, 18 females) or placebo ( n =25; 15 males, 10 females) for 12 weeks (12 sprays/day max. based on clinical response/tolerability). The primary outcome was change from baseline in level of spasticity on a 0 to 10 Numerical Rating Scale (NRS), assessed by the primary caregiver at 12 weeks. Secondary outcomes included additional measures for spasticity, sleep quality, pain, health‐related quality of life, comfort, depression, and safety. Results: There was no significant difference in the spasticity 0 to 10 NRS between nabiximols versus placebo groups after 12 weeks. No statistically significant differences were observed for any secondary endpoint. Adverse events were predominantly mild or moderate in severity; however, three cases of hallucinations were reported. Interpretation: Nabiximols was generally well tolerated; however, neuropsychiatric adverse events were observed. No significant reduction in spasticity with nabiximols treatment versus placebo was observed. What this paper adds: Oromucosal nabiximols is generally well tolerated by paediatric patients. However, three cases of hallucinations were observed, one of which involved auditory hallucinations and a suicide attempt. Oromucosal nabiximols versus placebo did not reduce cerebral palsy/central nervous system injury‐related spasticity. What this paper adds: Oromucosal nabiximols is generally well tolerated by paediatric patients. However, three cases of hallucinations were observed, one of which involved auditory hallucinations and a suicide attempt. Oromucosal nabiximols versus placebo did not reduce cerebral palsy/central nervous system injury‐related spasticity. This article is commented on by Hall and Nielsen on page 1007 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Eficacia y seguridad de cannabinoides nabiximol para el manejo de la espasticidad en pacientes pediátricos con parálisis cerebral o lesión cerebral traumática: un ensayo controlado aleatorio: Objetivo: Evaluar la eficacia, seguridad y tolerabilidad del cannabinoides nabiximol de aplicación en spray bucal como terapia complementaria para niños con espasticidad debido a parálisis cerebral o lesión traumática del sistema nervioso central que no responden al tratamiento convencional. Método: En total, 72 pacientes (media [DE] edad 12 años 4 meses [3 años 1 mes], rango 8‐18 años) fueron aleatorizados en una proporción de 2: 1 para recibir nabiximol spray (n = 47; 29 masculinos, 18 femeninos) o placebo (n = 25; 15 masculinos, 10 femeninos) durante 12 semanas (12 aplicaciones de spray / día máx basados en la respuesta clínica / tolerabilidad). El resultado primario fue el cambio en el nivel basal de espasticidad en una Escala de Calificación Numérica (NRS) de 0 a 10, evaluada por el cuidador primario a las 12 semanas. Los resultados secundarios incluyeron medidas adicionales para la espasticidad, la calidad del sueño, el dolor, la calidad de vida relacionada con la salud, el confort, la depresión y la seguridad. Resultados: No hubo diferencias significativas en la espasticidad de 0 a 10 NRS entre los grupos de que recibieron nabiximol versus el grupo placebo después de 12 semanas. No se observaron diferencias estadísticamente significativas para ningún criterio de valoración secundario. Los eventos adversos fueron predominantemente leves o moderados en severidad; sin embargo, se informaron tres casos de alucinaciones. Interpretación: El nabiximol fue generalmente bien tolerado; sin embargo, se observaron eventos adversos neuropsiquiátricos. No se observó una reducción significativa en la espasticidad con el tratamiento con nabiximoles versus placebo. Eficácia e segurança do medicamento nabiximols canabinóide para espasticidade pediátrica em paralisia cerebral ou lesão cerebral traumática: um estudo clínico randomizado: Objetivo: Avaliar a eficácia, segurança e tolerabilidade do medicamento oromucosal nabiximols canabinóide como terapia adjunta para crianças com espasticidade devida a paralisia cerebral/lesão traumática do sistema nervoso central com resposta inadequada a tratamentos existentes. Método: Em geral, 72 pacientes (média [DP] idade 12a 4m [3a 1m], variação 8‒18a) foram randomizados em uma taxa de 2:1 para receber nabiximols ( n =47; 29 sexo masculino, 18 sexo feminino) ou placebo ( n =25; 15 sexo masculino, 10 sexo feminino) por 12 semanas (12 sprays/dia máx. com base na resposta clínica/tolerabilidade). O resultado primário foi mudança com relação a linha de base no nível de espasticidade um uma Escala Numérica de Pontuação (ENP) de 0 a 10, avaliada pelo cuidador primário com 12 semanas. Resultados secundários incluíram medidas adicionais de espasticidade, qualidade do sono, dor, qualidade de vida relacionada à saúde, conforto, depressão, e segurança. Resultados: Não houve diferença significativa na espasticidade Segundo a ENP 0 a 10 entre os grupos nabiximols versus placebo após 12 semanas. Nenhuma diferença estatisticamente significativa foi observada para nenhum desfecho secundário. Eventos adversos foram predominantemente leves ou moderados em severidade; no entanto, três casos de alucinações foram reportados. Interpretação: Nabiximols foi em geral bem tolerado; no entanto eventos adversos neuropsiquiátricos foram observados. Nenhuma redução significativa na espasticidade com o tratamento com nabiximols versus placebo foi observada.